Using English Songs in Teaching Biology 10 to Develop Student´s Foreign Language Competence - Ly, Lai Ngoc; Quynh, Nguyen Thi Thuy (VNU Journal of Science: Education Research, 2020)
Although the application of English songs in teaching Biology is one of the new teaching methods in Vietnam, it can become an effective method to help the students change both their looks and their ways to approach the natural science curriculum. The combination of smooth melodies and easy-to-remember content of the songs will help students easily remember general knowledge of the lesson. Moreover, the content of English songs will help them understand, memorize special vocabulary effectively, and improve their foreign language skills. A statistical investigation on the status of teaching Biology in English was carried out at some high schools in Hanoi. Several English songs had been used in teaching Biology grade 10. Pedagogical experiments have shown that Biology songs in English will benefit to create interest in learning and especially help them memorize biological terms in English easily.